Three new Indo-West Pacific species of coral reef mantis shrimps (Stomatopoda: Gonodactylidae) - Ahyong, Shane T. (Zootaxa, 2026)
Species of the family Gonodactylidae Giesbrecht, 1910 are the dominant mantis shrimps on tropical Indo-West Pacific coral reefs. Two species of Gonodactylellus Manning, 1995 and one new species of Gonodactylus Berthold, 1827 are formally documented as new to science. Gonodactylellus aor sp. nov. is described from off southern Peninsular Malaysia and most closely resembles Gonodactylellus erdmanni Ahyong, 2001 and G. incipiens (Lanchester, 1903) but is readily distinguished by the presence of the distinct knob of the telson, which is visible in dorsal view and protrudes slightly beyond the apex of the median carina. Gonodactylellus kirki sp. nov. from Tonga, a member of the G. molyneux group, is unique in the genus in the presence of rounded and bulbous dorsal projections at the base of the submedian and intermediate teeth of the telson, and unusual in lacking the fixed distoventral spine on the proximal article of the uropodal exopod (a condition otherwise feature known only in G. choprai (Manning, 1967)) and G. kandi Ahyong & Erdmann, 2007. More significantly, the unusual telson structure of G. kirki is the strikingly similar to that of members of Gonodactylopsis Manning, 1969 and Hoplosquilla Holthuis, 1964, particularly Gonodactylopsis komodoensis Erdmann & Manning, 1998 and Hoplosquilla said Erdmann & Manning, 1998; these shared similarities corroborate the contention that the G. molyneux group is probably more closely related to Gonodactylopsis and Hoplosquilla than to other members of Gonodactylellus. Gonodactylellus kirki is the only member of the G. molyneux group known to naturally occur on oceanic islands (one species introduced to Hawaii); all other members of the G. molyneux group are known from reef habitats along the continental margins. Gonodactylus roycaldwelli sp. nov., described from eastern Australia and the Coral Sea, most closely resembles Go. smithii Pocock, 1893, differing chiefly in the much more elongated accessory median carinae of the telson, and in its apparently strictly subtidal rather than intertidal and shallow subtidal occurrence. As a result of the present study, 28 species of Gonodactylellus and seven species of Gonodactylus are now recognised.